2020
DOI: 10.1134/s0031918x20060162
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Deformation in Coarsening of M23C6 Carbide Particles in 9% Cr Steel

Abstract: The kinetics of the growth of M 23 C 6 carbide particles in 9% Cr steel of the martensitic class with a high content of boron is studied under conditions of prolonged aging and creep. It is shown that the grainboundary diffusion is a mechanism that controls the coagulation of these carbides in the case of annealing. Deformation accelerates the enlargement of particles during creep, which is explained by additional diffusion along dislocation lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…that atomic diffusion would be encouraged in the fine grain region during aging, resulting in the promotion of precipitate coarsening 41) . In addition, effects of the initial distribution of precipitates are considered 42) .…”
Section: Discussionmentioning
confidence: 99%
“…that atomic diffusion would be encouraged in the fine grain region during aging, resulting in the promotion of precipitate coarsening 41) . In addition, effects of the initial distribution of precipitates are considered 42) .…”
Section: Discussionmentioning
confidence: 99%
“…Tkachev etal. 62 reported that the coarsening of M 23 C 6 transpired due to their interaction with dislocations and the occurrence of grain boundary diffusion mechanism.…”
Section: Stir Zone Microstructuresmentioning
confidence: 99%
“…The work done by the external force on the deformation zone during high-temperature stretching caused the temperature of it to be higher than tensile temperature, which provided thermodynamic conditions for the redissolution of small carbides near the fracture zone and the grain growth of large carbides [25,26]. Due to the low thermal activation energies of M 7 C 3 and M 23 C 6 carbides [27], Cr-containing carbides grew significantly during high-temperature stretching.…”
Section: Precipitate Phase Analysismentioning
confidence: 99%